Gravimetry and economic approach of municipal solid waste from Barra de São Miguel county – Paraíba - Araújo, Narcísio Cabral de; Queiroz, Abílio José Procópio; Guimarães, Pablo Luiz Fernandes; Gomes, Antônia Araújo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Barra de São Miguel is a municipality located in the micro region of the state of Paraiba Eastern Cariri. It is one of many municipalities that do not properly manage their solid waste, only collects, transports and dumps garbage dump in the open. The objectives are to analyze the gravimetric composition of municipal solid waste produced in the municipality of Barra de São Miguel, PB and evaluate the waste of economic value that this material is provided can be retrieved. The results showed a per capita production 0.6049 kg. per-1. day-1, and total daily urban production 1430.07 kg. On average they are wasted daily R $ 112.10 due to the poor management of urban solid waste. However with proper management, the funds raised through this material would give financial support to the activities of solid waste management in the municipality. The need to make the dissemination of environmental education It can be seen in the city, to changing habits of its residents as well as the implementation of an integrated management system of municipal solid waste, reversing the environmental, social and economic impacts on benefits.